One CGIAR and the Integrated Agri-food Systems Initiative: From short-termism to transformation of the world’s food systems - Govaerts, Bram; Negra, Christine; Camacho Villa, Tania Carolina; Chavez Suarez, Xiomara; Espinosa, Anabell Diaz; Fonteyne, Simon; Gardeazábal Monsalve, Andrea; González, Gabriela; Gopal Singh, Ravi; Kommerell, Víctor; Kropff, Wietske; López Saavedra, Víctor; et al. (Public Library of Science, 2021)
Agri-food systems are besieged by malnutrition, yield gaps, and climate vulnerability, but integrated, research-based responses in public policy, agricultural, value chains, and finance are constrained by short-termism and zero sum thinking. As they respond to current and emerging agri-food system challenges, decision makers need new tools that steer toward multi-sector, evidence-based collaboration. To support national agri-food system policy processes, the Integrated Agri-food System Initiative (IASI) methodology was devel oped and validated through case studies in Mexico and Colombia. This holistic, multi-sector methodology builds on diverse existing data resources and leverages situation analysis, modeled predictions, and scenarios to synchronize public and private action at the national level toward sustainable, equitable, and inclusive agri-food systems. Culminating in collec tively agreed strategies and multi-partner tactical plans, the IASI methodology enabled a multi-level systems approach by mobilizing design thinking to foster mindset shifts and stakeholder consensus on sustainable and scalable innovations that respond to real-time dynamics in complex agri-food systems. To build capacity for these types of integrated, con text-specific approaches, greater investment is needed in supportive international institu tions that function as trusted in-region ‘innovation brokers.’ This paper calls for a structured global network to advance adaptation and evolution of essential tools like the IASI methodol ogy in support of the One CGIAR mandate and in service of positive agri-food systems transformation.